Ten years' experience with four cycles of bleomycin, etoposide, doxorubicin, cyclophosphamide, vincristine, prednisone, procarbazine (BEACOPP)-escalated followed by four cycles of baseline-dose BEACOPP in patients with advanced stage Hodgkin lymphoma: a single-center, retrospective study - Belada, David; Štěpánková, Pavla; Sýkorová, Alice; Žák, Pavel; Smolej, Lukáš (Leukemia & lymphoma, 2015)
The HD-9 trial showed that eight cycles of BEACOPP (bleomycin, etoposide, doxorubicin, cyclophosphamide, vincristine, prednisone, procarbazine)-escalated led to significant improvements in response rate, progression-free survival and overall survival over COPP/ABVD (cyclophosphamide, vincristine, prednisone, procarbazine/doxorubicin, bleomycin, vinblastine, dacarbazine) therapy. This monocentric retrospective study was performed to evaluate 10 years of experience with four cycles of BEACOPP-escalated and four cycles of BEACOPP-baseline outside of clinical trials. The outcomes were assessed in 78 patients with newly diagnosed advanced stage Hodgkin lymphoma. A complete response after chemotherapy ± radiotherapy was achieved in 75 patients (96%). At the median follow-up of 74 months, the actuarial 5- and 10-year freedom from treatment failure (FFTF) rates were 91% and 89%, and actuarial 5- and 10-year overall survival rates for the entire group were 93% and 90%, respectively. These results suggest that the combination of escalated and baseline BEACOPP chemotherapy is feasible in routine practice with good efficacy and acceptable toxicity.
Keywords: prokarbazin; bleomycin; Dose-Response Relationship, Drug; Doxorubicin; vztah mezi dávkou a účinkem léčiva; BEACOPP chemotherapy; cyklofosfamid; prednison; Retrospective Studies; Prognosis; Time Factors; mladiství; Middle Aged; mužské pohlaví; advanced stage; toxicity; Neoplasm Recurrence, Local; míra přežití; Adult; mladý dospělý; Hodgkin Disease; lokální recidiva nádoru; Bleomycin; Vincristine; Hodgkin lymphoma; Follow-Up Studies; následné studie; Neoplasm Staging; Young Adult; doxorubicin; ženské pohlaví; prognóza; Cyclophosphamide; retrospektivní studie; Humans; Procarbazine; Prednisone; Etoposide; Survival Rate; časové faktory; lidé středního věku; etoposid; vinkristin; Antineoplastic Combined Chemotherapy Protocols; Hodgkinova nemoc; staging nádorů; protokoly protinádorové kombinované chemoterapie; dospělí; Female; Adolescent; lidé; Male